Positional isomerism for strengthening intermolecular interactions: Toward monocyclic nitramino oxadiazoles with enhanced densities and energies - Sun, Qi; Ding, Ning; Zhao, Chaofeng; Ji, Jie; Li, Shenghua; Pang, Siping (Chemical engineering journal (Lausanne, Switzerland : 1996), 2022)
•Positional isomerism is a promising strategy to enhance the densities of energetic materials.•The density of the isomer is more than 0.08 g cm-3 higher than that of original material.•Crystal structures and intermolecular interactions were studied to investigate the mechanism. Development of high-density energetic materials has drawn considerable attention because the densities significantly affect their detonation performance. Herein, we propose an effective strategy based on positional isomerism for enhancing the densities of pre-existing energetic materials by optimizing their structures to reinforce intermolecular interactions. By applying this strategy, we design and synthesize 2-amino-5-nitramino-1,3,4-oxadiazole (2), a suitable isomer of 3-amino-5-nitramino-1,2,4-oxadiazole (1). This isomer is the first example of a monocyclic nitramino 1,3,4-oxadiazole reported to date. Single-crystal X-ray diffraction reveals that the isomer has a high crystal density (1.938 g cm−3 at 110 K), which is 0.083 g cm−3 greater than that of the original material (1, 1.855 g cm−3 at 110 K). Mechanistic studies confirmed that the isomer possesses stronger intermolecular hydrogen-bonding and π − π interactions, resulting in denser stacking, smaller cell volume, and thus, higher density. Remarkably, the isomer has a very short intermolecular hydrogen bond (1.956 Å), which is significantly shorter than that of 1 (2.133 Å) and other representative strongly hydrogen-bonded energetic materials such as 2,4,6-triamino-1,3,5-trinitrobenzene (TATB, 2.239 Å) and 1,1-diamino-2,2-dinitroethylene (FOX-7, 2.143 Å). Moreover, this strategy can be applied to its energetic salts. The higher densities of the isomer and its salts endow better detonation performance. Particularly, the detonation velocity of the isomer is more than 400 m s−1 higher than that of the original material (8668 m s−1 for 2 vs 8250 m s−1 for 1). Meanwhile, the hydroxylammonium salt 2b exhibits a high detonation velocity of 9087 m s−1, which is superior to that of 1,3,5-trinitroperhydro-1,3,5-triazine (RDX).